2019
DOI: 10.1242/dmm.041251
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of terminal hypertrophic chondrocyte differentiation in Prmt5 mutant mice modeling infantile idiopathic scoliosis

Abstract: Idiopathic scoliosis (IS) is the most common type of musculoskeletal defect affecting children worldwide, and is classified by age of onset, location and degree of spine curvature. Although rare, IS with onset during infancy is the more severe and rapidly progressive form of the disease, associated with increased mortality due to significant respiratory compromise. The pathophysiology of IS, in particular for infantile IS, remains elusive. Here, we demonstrate the role of PRMT5 in the infantile IS phenotype in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…However, the Sko mice are a novel and useful animal model that shows scoliosis with features similar to syndromic scoliosis since most genetically altered models of scoliosis are unclear about which type of scoliosis they resemble in humans or die soon after birth. [21,22] Furthermore, this is the first basic science report to demonstrate the causal relationship between scoliosis and reduced bone density and quality, to our knowledge. Therefore, we believe that the insights gained from this study provide a clue to elucidating the etiology of scoliosis, which may lead to new treatment development for the disease.…”
Section: Characteristics Of Scoliosis In Mice • Handa Et Almentioning
confidence: 76%
See 2 more Smart Citations
“…However, the Sko mice are a novel and useful animal model that shows scoliosis with features similar to syndromic scoliosis since most genetically altered models of scoliosis are unclear about which type of scoliosis they resemble in humans or die soon after birth. [21,22] Furthermore, this is the first basic science report to demonstrate the causal relationship between scoliosis and reduced bone density and quality, to our knowledge. Therefore, we believe that the insights gained from this study provide a clue to elucidating the etiology of scoliosis, which may lead to new treatment development for the disease.…”
Section: Characteristics Of Scoliosis In Mice • Handa Et Almentioning
confidence: 76%
“…The incidence of scoliosis due to cartilage-related abnormalities has recently attracted much attention, and loci associated with cartilage, such as GPR126 and PAX1, have been detected in genome-wide association studies 3,21 . Furthermore, it has been reported that chondrocyte-specific inactivation of Prmt5 and SHP2 in mice results in IS 22,23 . Growth plate thickening has also been observed in scoliosis in mice with Prmt5 inactivation, and impaired endochondral ossification causes scoliosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal preparations were performed as previously described 65 . Briefly, P1 pups were skinned and fixed in 10% neutral-buffered formalin for 1 day at 4°C, stained with 0.3% Alcian blue and 0.1% Alizarin red at 37°C for 3 days, and cleared with 1% KOH.…”
Section: Analyses Of Micementioning
confidence: 99%
“…Congenital disorders can specifically affect single-organ systems, such as the heart (reviewed by Rufaihah et al, 2021), kidneys (reviewed by Blackburn and Miller, 2019), as well as skeleton and muscles (Liu et al, 2019;Rios et al, 2021;Wong et al, 2020). Patients with congenital bicuspid aortic valve have two instead of three flaps in this valve, which can lead to disease of this major artery.…”
mentioning
confidence: 99%